2007
DOI: 10.15381/rpb.v14i2.1794
|View full text |Cite
|
Sign up to set email alerts
|

Capacidad entomocida de cepas nativas de Beauveria sp. sobre Schistocerca piceifrons peruviana (Lynch Arribalzaga, 1903)

Abstract: ResumenCuatro cepas de Beauveria sp. (ABvPr11, ABvPr8, ABvPr3 y ABvSr4), fueron aisladas y caracterizadas de ejemplares de la langosta Schistocerca piceifrons peruviana procedentes de la Provincia de Huamanga del Departamento de Ayacucho. La capacidad entomocida de las 4 cepas fue evaluada en la langosta Schistocerca piceifrons peruviana. Los resultados muestran que todas las cepas, en soluciones de 10 8 conidias/mL, producen un 100% de mortalidad. El tiempo que se necesitó para eliminar el 100% de las langost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…At the same environmental conditions, we have previously showed that a 10 8 concentration of the Pr-11 strain was effective against the cotton pest Dysdercus peruvianus (Hemiptera:Pyrrhocoridae), reporting a LT50=5,6 days and 19,2 days and outperforming other 50 fungal isolates (Falconi et al, 2010). Similarly, Pariona et al (2007) showed promising results of this strain against S. piceifrons, at a 10 8 conidial concentration, resulting in a LT50=8.34 and LT80=9.6 days. These results indicate that B. bassiana may be more pathogenic against hosts other than the original one.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…At the same environmental conditions, we have previously showed that a 10 8 concentration of the Pr-11 strain was effective against the cotton pest Dysdercus peruvianus (Hemiptera:Pyrrhocoridae), reporting a LT50=5,6 days and 19,2 days and outperforming other 50 fungal isolates (Falconi et al, 2010). Similarly, Pariona et al (2007) showed promising results of this strain against S. piceifrons, at a 10 8 conidial concentration, resulting in a LT50=8.34 and LT80=9.6 days. These results indicate that B. bassiana may be more pathogenic against hosts other than the original one.…”
Section: Discussionmentioning
confidence: 83%
“…The Beauveria bassiana PR-11 strain was isolated from adult and nymphs of S. piceifrons, in the locality of Huamanga (Ayacucho), located at 2761 m.a.s.l. in the central Andean region of Peru (Pariona et al, 2007). This strain was named "PR" as this was the first of three insect sampling campaign (primera recolecta) and number 11 correspond to the 11th S. piceifrons specimen.…”
Section: Preparation Of Fungimentioning
confidence: 99%
“…Además se empleó la cepa de Beauveria sp. PR-11 aislada de Schistocerca piceifrons peruviana procedente de Ayacucho (Pariona et al 2007). …”
Section: Materials Y Métodosunclassified
“…presentó una colonia con micelios blancos de aspecto algodonoso y superficie semielevada. Se observó la formación de sinemas reportadas por Vargas (2003) para Beauveria bassiana y por Pariona (2007) para Beauveria sp. En el cultivo produjo un pigmento de color amarillo, que evidenció la producción de la toxina Bauvericina (Gómez 1998, Vargas 2003.…”
Section: Caracterización Morfológica De Los Hongosunclassified
“…Los géneros Beauveria y Metarhizium han evidenciado buenos resultados en el control de otras plagas tropicales (Reyes et al, 1995;France et al, 1999;Nankinga y Moore, 2000;Godonou et al, 2000;Giraldo, 2001;Pariona et al, 2007;Góngora, 2008).…”
Section: Introductionunclassified